SELF-ACCEPTANCE AND RELIGIOSITY: COMBATING LONELINESS IN ADOLESCENTS - Fitriyani, Azizah Nur; Saloom, Gazi (Al-Tazkiah Jurnal Bimbingan dan Konseling Islam, 2025)
This research aims to test the influence of self-acceptance and religiosity on loneliness in adolescents. This research uses quantitative methods with multiple regression analysis. The subjects of this research were 405 adolescents aged 18-22 years who lived in Jabodetabek. The data collection technique uses a non-probability sampling method with accidental sampling type. The author used the UCLA Loneliness Scale Version 3 as a measuring tool for loneliness, the Berger Self-Acceptance Scale as a measuring tool for self-acceptance, and the Centrality of Religiosity Scale (CRS) as a measuring tool for religiosity. The results of this research show that there is a significant influence of self-acceptance and religiosity on loneliness in adolescents, with a contribution of 41.2%. When self-acceptance and religiousness are high, the level of loneliness among teens is low.